Stabilisation of a plastic soil with alkali activated cements developed from industrial wastes - Cristelo, Nuno (2021)
The development of alternative materials for the construction industry, based on different types of waste, is gaining significant importance in recent years. This is mostly due to the need to increase sustainability of this heavily polluting activity, thus mitigating the dependence on, for instance, Portland cement. The present paper is related to the development of an alkaline activated cement (AAC) exclusively fabricated from industrial by-products (both precursor and activator). Coal combustion fly ash, a common residue from thermoelectric powerplants, and glass waste, from the manufacture of ophthalmic lenses, were used as precursors. These precursors were activated with a recycled alkaline solution, resulting from the cleaning of aluminium extrusion dies, instead of the more common commercial reagents usually applied for this type of binder. Several pastes were studied, combining the precursor and alkaline solution in different proportions. When the most-performing cements were defined, they were used to stabilise a cohesive soil. The experimental procedure and subsequent analysis were designed based on a Response Surface Methodology model, considering the Activator/Solids and Soil/Precursor ratios as the most relevant variables of the stabilisation process. It was observed that, depending on the type of alkaline cement used, there was an optimum precursor and activator contents to optimise the mechanical properties of the stabilised soil. The reliability of this prediction was especially dependent on the type of precursors and, also, on their respective dissolution process right before the homogenization with the soil, under the working conditions available.